'Don't kill them, let's choose them as wives': the development of the crimes of forced marriage, sexual slavery and enforced prostitution in international criminal law. Issue 3 (2nd April 2016) - O'Brien, Melanie
Abstract : Beyond rape, there are other crimes of sexual violence committed during armed conflicts, mass violence and genocide, including sexual slavery, enforced prostitution and forced marriage. This article explores the development in international criminal justice of these three crimes, comparing differences between the crimes, assessing any definitional overlap, and addressing challenges across jurisdictions. While there has been some development of jurisprudence in international criminal courts and tribunals, despite the extensive commission of these crimes in mass atrocities, there remains a lack of willingness by and to some extent inability of international courts and tribunals to address gender-based sexual offences. This article will conclude by confronting reasons behind this reluctance to ensure justice for female victims of sexual violence.